Availability and Price Volatility of Rice in Bangladesh: An Inter-Institutional Study in 2020 - Jahangir Alam; Md. Abdus Salam; Md. Abdur Rouf Sarkar; Mohammad Chhiddikur Rahman; Syful Islam; Md. Saidur Rahman; Md. Mahbubur Rahman; Mohammad Reza Ahmed Khan; Md. Raihan Obaidulla; Shaleha Khatun; Md. Anwar Hossen Khan; Md. Mosharraf Uddin Molla (Availability and price volatility of rice, potato and onion in Bangladesh, 2020)
Bangladesh has made remarkable progress in rice production and achieved self-sufficiency for feeding the people of Bangladesh. Total rice production in Bangladesh was 10.59 million tons in 1971 when population was 7.88 million, and increased to 38.72 million tons in 2020, which is three times more than previous production to feed her 170 million people. The growth of rice production (2.83%) was much faster than the growth of population (2.04%). In most recent days, market prices go up unexpectedly that poses threat to farmers and consumers, which is most embarrassing for the government and policy makers. Therefore, this research was recommended to find out the major drivers for rice price hikes in Bangladesh. Primary and secondary data were used in the analyses. The primary data were collected by conducting a telephonic survey and focus group discussion (FGD) and Key Informant Interview (KII). Secondary data were gathered from different organizations and the published sources. Suitable statistical and mathematical tools were employed to analyze the data. The growth rate of national rice production was always more than 2 percent in 1973-2000 and 2001-2020 while the growth rate over the period of 1973-2020 was 2.83 percent. To drive the growth of rice production upward, a package of intervention such as rapid spread of superior varieties, increment of irrigation areas under rice cultivation, adoption of climate resilient genotype, and better resource management and use of superior technologies, quality seeds and mechanization is required. During the two intervals of 2011-2015 and 2016-20, a substantial surplus of rice per capita was achieved. Almost 2 million tons remained surplus over the period 2009-2017 and more than 3 million tons over the years 2018 to 2020. The additional import of rice usually increased the national surplus and helped stabilize the market price of rice. Nominal price of rice increased, on average, at the rate of 4 to 5 percent whereas the real price decreased, on average, at the rate of 2 to 3 percent over the reference years (1972-2020). Even though the slope of nominal price in both T. Aman and Boro seasons was similar at all actor's level, adjustment of inflation in price of T. Aman paddy exhibits the higher market risk compared to that of Boro paddy. Cost of paddy cultivation was increasing at the rate of about 3 percent over the period of 2009-2020 while net profit (Tk/kg) was decreasing at the rate of about 8 percent over that period. The millers thought that they are the losers in rice processing business but they did not take the value of its by-products in their calculation. With valuation of by-products, millers usually made the profit per kg ranging from Tk. 4.6 in 2019 to 9.5 in 2017 in T. Aman while they made profit, from Tk. 4.7 in 2020 to 8.2 in 2018 in Boro season. Since market price of paddy usually exists below the procurement price, most of the farmers do not get the benefit of procurement price since government bought a few amount of paddy. However, farmers were happy to receive a good price of paddy in T. Aman, 2020. Historical trend of wholesale price was similar to that of procurement price of milled rice. The overall relationship between marketed surplus and price (figure 14) showed that someone might have power to regulate the determination of price in the market instead of market forces of supply and demand. Price spread reveals that midstream actors particularly millers, aratdars, and wholesalers harvested a super normal profit. In 2016, a reverse trend of price between Bangladesh and neighboring countries was observed. But almost a similar price trend appeared between 2017 and 2018. After that period, rice price in Bangladesh fell down lower than the import parity price of neighboring countries. However, the price increased in 2020 (figure 13). Public stock of rice drastically fluctuates and highly declines sometimes that gives an important signal of retention of minimum stock and increasing it to a minimum of 2500 thousand tons annually with a retention of at least 1250 thousand tons monthly. Highest prices in wholesale market of T. Aman were recorded in the month of January, February, June and October for the years 2016 through 2020 while in Boro, highest prices were recorded in January, March, September, October and December. Based on production situation, import decision, and domestic procurement, the value chain actors (millers and traders) make a gambling role to control price level of paddy and rice in the market. The indices during the period from 2016 to 2020, showed higher and unpredictable trend of paddy price from August to October. To control market prices during that period, the government should always maintain a large reserve of at least 12.5 lac tons of rice each month that would smoothen the impacts of large swings of rice prices. Almost all of the farmers used to sell major portion of marketable surplus within the first month of harvesting. The pattern of paddy sale changed substantially between the last two consecutive Boro seasons. In Boro 2020, farmers released their paddy stock a bit slowly in the market. The traders and millers, apprehending a panic of food shortage during pandemic, failure of rice procurement and import by the government, and speculation for higher price retained a part of their stockpiles of rice, which was the main reason for the price hike. The other reasons for price hike in rice market during 2020 includes supremacy and unequal competition of large millers and traders, delayed harmonization of data that led to the panic of shortage of paddy production, postponing rice import decision, increasing cost of paddy cultivation and rice processing, increasing number of seasonal traders and production loss from the disaster. Also the government stayed away from large intervention in the market during the stressed period. To overcome the seasonal price hikes; an up-gradation of paddy/rice procurement system is necessary. Government should declare separate minimum support prices (MSP) for fine and coarse grains of paddy and rice that will help farmers to get higher price at the harvesting time. The government should procure about 10 percent of total production with no less than 25 lac tons of rice so that intervention in the market can be made effectively. Government should retain at least 12 lac and 50 thousand tons of rice every month as buffer stock. Procurement price should be determined considering at least 20 percent profit over the production cost. Millers and traders should have trust on government data and should adjust their business strategy with the policy intervention of the government. Government should take more input support program so that all farmers get it like fertilizer subsidy. Concern ministry and department should have a policy to communicate with the rice millers and traders on regular basis so that a fair business environment prevails in this market. Finally, cost minimization strategy, intensive market monitoring, regulation for rice processing industries and timely government interventions are the important factors for ensuring stability in the market.
Keywords: 330; Price hike; Rice; Bangladesh; COVID-19; Cost of production; Demand-supply